2017
DOI: 10.1080/14789450.2017.1365602
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic studies in the discovery of cerebrospinal fluid biomarkers for amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive degenerative motor neuron disease, which usually leads to death within a few years. The diagnosis is mainly based on clinical symptoms and there is a need for ALS-specific biomarkers to make an early and precise diagnosis, for development of disease-modifying drugs and to gain new insights into pathophysiology. Areas covered: In the present review, we summarize studies using mass spectrometric (MS) approaches to identify protein alterations in the cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…Proteomics analysis of FTD and ALS has been conducted primarily in CSF with limited reproducibility across studies 16,[28][29][30][31] . To date, no studies have been reported for FTD using serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics analysis of FTD and ALS has been conducted primarily in CSF with limited reproducibility across studies 16,[28][29][30][31] . To date, no studies have been reported for FTD using serum or plasma.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature, including various proteomic studies, has helped to demonstrate that CSF composition in ALS may be abnormal ( Barschke et al , 2017 ; Blasco et al , 2017 ; Hayashi et al , 2019 ). This includes findings of raised TDP-43 and neurofilament levels, as well as an altered inflammatory profile ( Majumder et al , 2018 ; Schreiber et al , 2018 ; Gille et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, a variety of powerful quantification tools integrating novel align-ment and feature generation methods have been constructed to maximally fill in missing blanks and elevate the reproducibility of LFQ (17)(18)(19). On the other hand, many computational algorithms have been proposed to minimize the instrumental and experimental fluctuations (5), enhance the stability of the identified candidate markers (20), and reduce the extremely large dynamic range of the protein abundance (21). Specifically, Ն18 quantification software tools and Ն3 transformation, Ն18 pretreatment, and Ն7 missing-value imputation methods have been proposed and sequentially integrated into the quantification workflow to overcome the above challenges to the extent possible (supplemental Table S1).…”
mentioning
confidence: 99%